Effectiveness of the BNT162b2 and the CoronaVac vaccines and boosters in healthcare workers - Hazal Cansu Çulpan; Sümeyye Nur Aydın; Abdulkerim Uygur; Uğurcan Sayılı; Erkam Şeker; İ̇lker İnanç Balkan; Rıdvan Karaali; Beyhan Budak; Yılmaz Keskindemirci; Neşe Saltoğlu; Günay Can (Taylor & Francis Group, 2023)
ABSTRACTThe evidence on the waning protection of COVID-19 vaccines has been reviewed by the World Health Organization and has led to consideration of the need for booster doses. This study aimed to evaluate vaccine effectiveness against COVID-19, and the COVID-19 infections among healthcare workers who received various types (inactive or m-RNA) and doses (2 to 4 doses) of the COVID-19 vaccine. The study was conducted with a total of 3,009 healthcare workers between August 1 and November 30, 2021 at a university hospital. Six different vaccination statuses were evaluated in the study. The effectiveness for COVID-19 infection, after adjusting for age, sex, and position, was highest in those who received two doses of CoronaVac and two doses of BNT162b2 (89.3%, 95% CI 72.2-95.9%) and was lowest in those who received two doses of CoronaVac (29%, 95% CI − 8-53%). The adjusted effectiveness of two doses of CoronaVac for COVID-19 infection was not significant (21.0%, 95% CI − 20.7-48.3%) but increased significantly with a booster dose of CoronaVac or BNT162b2. One or two doses of the BNT162b2 booster demonstrated higher effectiveness in comparison to a single dose of the CoronaVac booster. These results indicate the need for a booster dose, and heterologous boosting with BNT162b2 may be a better option for higher effectiveness for those who received two doses of CoronaVac. Future studies should evaluate the need for further booster doses and their long-term effects.